Evaluation of Posterior Malleolar Fractures and the Posterior Pilon Variant in Operatively Treated Ankle Fractures. (September 2014) - Switaj, Paul J.; Weatherford, Brian; Fuchs, Daniel; Rosenthal, Brett; Pang, Eric; Kadakia, Anish R.
Background: Substantial attention has recently been placed on fractures of the posterior malleolus. Fracture extension to the posteromedial rim ("posterior pilon variant") may result in articular incongruity and talar subluxation. Current classification systems fail to account for these fractures. The relative frequency of this fracture, its associated patient characteristics, and the reliability of its diagnosis have never been reported in such a large series. Methods: We retrospectively identified 270 patients who met our inclusion criteria. Basic demographic data were collected. The fractures were classified according to Lauge-Hansen and AO/OTA. Additional radiographic data included whether the fracture involved the posterior malleolus and whether the fracture represented a posterior pilon variant. Univariate statistical methods, chi-square analysis, and interobserver reliability were assessed. Results: The relative frequency of posterior malleolus fracture was 50%. The relative frequency of the posterior pilon variant was 20%. No significant difference was noted with respect to the frequency of posterior malleolar or posterior pilon variant between the subgroups of the AO/OTA and Lauge-Hansen classification systems when compared to the overall fracture distribution. Patients with posterior malleolar fractures and posterior pilon variants were significantly older. Females were significantly more likely than men to sustain posterior malleolar fractures and posterior pilon variants. Patients with diabetes trended toward a greater risk of both types of fractures. Interobserver reliability data revealed substantial agreement for posterior malleolar fractures and posterior pilon variants. Conclusion: These data represent the highest reported rate of posterior malleolar involvement in operatively treated ankle fractures and is the first to describe the percentage of the posterior pilon variant in such a large series. The interobserver reliability data demonstrate substantial agreement in identification of posterior malleolar fractures and the posterior pilon variant based on plain radiographs. Certain patient characteristics such as age, sex, and diabetes may be associated with these fractures. Level of Evidence: Level III, retrospective cohort study.